2003
DOI: 10.1260/030952403773617472
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Yield of Roof Mounted Wind Turbines

Abstract: The roof is a possible site for small wind turbines. This is a new but more and more accepted idea. Several Dutch companies in close cooperation with the Section Wind Energy of Delft University of Technology are busy with the design of small roof wind turbines at the moment. The important flow features for a wind turbine on the roof however are unknown. The common wind engineering knowledge is only focussed on extreme wind speeds in order to have a safe building. So, models to calculate the flow features on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 5 publications
0
53
0
2
Order By: Relevance
“…Mertens [4] examined the parameters that effected small-scale roof mounted wind turbines. Flow features of an urban landscape were inspected for applying a roof mounted wind turbine.…”
Section: Previous Related Workmentioning
confidence: 99%
“…Mertens [4] examined the parameters that effected small-scale roof mounted wind turbines. Flow features of an urban landscape were inspected for applying a roof mounted wind turbine.…”
Section: Previous Related Workmentioning
confidence: 99%
“…Dayan [27] suggested the mounting of wind turbines on top of high-rise buildings for a greater opportunity for wind energy generation in an urban area, and on buildings with special roof shapes [28]. The shape of buildings offers the possible benefits by augmentation of wind flow around buildings for wind energy generation as theoretically identified by Mertens [29]. Dutton et al [30] suggested that the locations of the acceleration effects over different roof shapes should be investigated in order to take advantage of the increased wind speed which translates into more energy yield.…”
Section: Building Integrated Wind Turbinesmentioning
confidence: 99%
“…To convert the wind atlas speed into a local reference speed, Mertens [9] suggests treating the edge of the urban area as a step change in roughness. Upwind of the urban boundary, the wind has a speed at height z A of U A (z A ), as given in the atlas, and a profile determined by a surface roughness length z 0A of 0.03m.…”
Section: Finding a Reference Wind Speed From The Wind Atlasmentioning
confidence: 99%